Anxiety disorders in postpartum women: A systematic review and meta-analysis - Goodman, Janice H.; Watson, Grace R.; Stubbs, Brendon (Journal of affective disorders, 2016)
Evidence suggests that postpartum anxiety is relatively common among postpartum women. Anxiety meeting diagnostic criteria for a disorder represents anxiety at its most severe, distressing, and persistent, and thus it is most important to identify, understand, and treat. This paper describes a comprehensive systematic review of anxiety disorders among postpartum women, along with meta-analysis of prevalence. Findings are based on a thorough search of the literature, strict inclusion of only studies which utilized the gold standard of diagnostic interviews for anxiety disorder determination, and critical appraisal and review of included studies. A random effects meta-analysis was used to determine prevalence. Fifty-eight studies were included in the review: 13 addressed prevalence, 5 incidence, 14 onset, 16 course, 13 correlates and risk factors, 15 outcomes, and 2 treatments for postpartum anxiety disorders. An estimated 8.5% of postpartum mothers experience one or more anxiety disorders. Many limitations relate to the state of the current literature, including a small number of studies to answer specific research questions for each disorder, methodological limitations, and considerable heterogeneity across studies. Anxiety disorders are common among postpartum women. The review summarizes the current status of research on postpartum anxiety disorders and underscores the need for increased research to more accurately determine prevalence, understand course, identify risk factors and outcomes, and determine effective treatments. Greater clinical attention to these disorders is warranted to ameliorate the negative consequences of postpartum anxiety disorders on women and families. •This review included 58 studies which addressed anxiety disorders in postpartum women.•Postpartum anxiety disorders may be more common than is generally recognized.•An estimated 8.5% of postpartum mothers experience one or more anxiety disorders.•Research on postpartum anxiety disorders is still in its early stages.•Anxiety disorders may adversely affect the mother-infant relationship and infant outcomes.